ANALISIS MAKNA ASPEKTUAL HOJODOUSHI TE IKU DAN TE KURU - Gunadharma, - (2016)
Penelitian ini bertujuan untuk menjelaskan makna aspek yang muncul pada verba bantu te iku dan pada verba bantu te kuru, serta mengetahui makna aspek apa saja yang dinyatakan oleh verba bantu te iku dan te kuru yang terdapat dalam bahan ajar bahasa Jepang. Teknik analisis data yang digunakan dalam penelitian ini adalah metode kajian distribusional. Hasil analisis dalam penelitian ini menunjukkan makna aspek yang muncul pada verba bantu te iku sebanyak tiga makna, yaitu makna aspek inkoatif yang menunjukan penghilangan atau pemusnahan, makna aspek augmentatif yang menunjukan peningkatan intensitas pada suatu aksi atau keadaan, dan makna aspek progresif yang menunjukan keberlanjutan aksi dari satu titik waktu tertentu. Kemudian, makna aspek yang muncul pada verba bantu te kuru sebanyak empat makna, yaitu makna aspek inkoatif yang menunjukan mulainya suatu aksi atau aktivitas, makna aspek augmentatif yang menunjukan peningkatan intensitas pada suatu aksi atau keadaan, makna aspek inkoatif yang menyatakan munculnya suatu keadaan, dan makna aspek progresif yang menunjukan keberlanjutan aksi sampai pada satu titik waktu tertentu. Sedangkan hasil analisis makna aspek verba bantu te iku dan te kuru terdapat 22 buah makna.yang muncul pada buku ajar bahasa Jepang. Kata-kata kunci : makna aspektual, hojodoushi, te iku, te kuru, semantik This research aims to clarify the meaning of aspects that appear in Japanese auxiliary verb te iku and the auxiliary verb te kuru, and to know the meaning of aspects that expressed by the auxiliary verbs te iku and te kuru in Japanese language teaching materials. The data analysis techniques used in this research is the study of distributional. Results of analysis in this research shows, in the meaning of aspects that three meanings appear in the auxiliary verb te iku, it is the inchoative aspect meaning that shows the removal or destruction, the augmentative aspects meaning which showed an increase of intensity in an action or state, and the progressive aspect meaning that shows the sustainability of the action from a certain point of time. Then, in the meaning of aspects that four meanings appear in auxiliary verb te kuru, it is the inchoative aspect meaning which indicates the beginning of an action or activity, the augmentative aspects meaning which showed an increase in intensity in an action or state, the inchoative aspect meaning stating the emergence of a state, and meaning that shows the progressive aspects of the sustainability of action until at one point in time. And then, the results of the analysis of the meaning of auxiliary verb of aspect te iku and te kuru contained 22 meaning that appear in the Japanese textbook. Key words: the aspectual meaning, hojodoushi, te iku, te kuru, semantics